BUSINESS ACTORS’ RESPONSIBILITY TOWARDS CONSUMERS DUE TO DEFECTIVE PRODUCT - Adnyani, Ni Ketut Sari; Mangku, Dewa Gede (Veteran Law Review, 2019)
This study aims to examine the form of business actor?s responsibilities to consumers in terms of defective products, following up on efforts that can be taken if there are business actors who do not fulfill their responsibilities. The research method in normative and empirical legal research, and the type of research is a comprehensive analytical study of primary legal materials, secondary legal materials and tertiary legal materials. Using empirical legal research approach methods, the approarch is the statutory approach and the fact approach. The focus of normative legal research is an inventory of written positive law mainly concerning the regulation of the rsponsibilities of business actors in buying and selling in the perspective of the Consumer Protection Law No.8 of 1999, the Civil Code (KUHP), and regulations concerning defective products. Research is a descriptive study using qualitative. Determination of subjects in this study using Simple Random Sampling technique. Empirical legal research, targeting aspects of justice, usefulness, and legal certainty based on the Sociological Jurisprudence flow. Research results: Business actors are responsible if the product dects that occur are entirely wrong. The effort taken of the business actor does not want to be responsible for the occurrence of product defects in the sale and purchase transaction is by solving the Dispute Resolution and familial approach. If it doesn?t work, then it can be reached through a court. Keywords: defective products, business actors, protection, regulations.